Age‐related macular degeneration in Portugal: prevalence and risk factors in a coastal and an inland town. The Coimbra Eye Study – Report 2. (25th January 2016) - Cachulo, Maria da Luz; Laíns, Inês; Lobo, Conceição; Figueira, João; Ribeiro, Luísa; Marques, João P.; Costa, José; Vieira, António; Rodrigues, João; Alves, Dalila; Nunes, Sandrina; Costa, Miguel; et al.
Abstract: Purpose: To determine the age‐ and sex‐specific prevalence of early and late age‐related macular degeneration (AMD) in two Portuguese population‐based samples and to identify its risk factors. Population: A population of 6023 adults aged ≥55 years was recruited from two Portuguese primary healthcare units in the central region of Portugal – one from a coastal ( n  = 3000) and another from an inland town ( n  = 3023). Methods: Cross‐sectional population‐based study. Participants were enrolled in the two locations between August 2009 and October 2013. Responders underwent standardized interviews and ophthalmologic examination, including digital fundus imaging. All fundus photographs were graded according to an International Classification and Grading System. The main outcome measures consisted of age‐ and sex‐adjusted prevalence of early and late AMD. Potential epidemiologic risk factors were also evaluated using logistic regression analysis. Results: Of the 6023 subjects enrolled, 5996 had gradable fundus images and were included in the analysis. The crude prevalence of early and late AMD was 6.99 and 0.67%, respectively, for the coastal town and 15.39 and 1.29% for the inland town. Age‐ and sex‐adjusted prevalence of any AMD for the Portuguese population was 12.48% (95% CI: 11.61–13.33) with late AMD accounting for 1.16% (95% CI: 0.85–1.46). Neovascular AMD (NV‐AMD) and geographic atrophy (GA) accounted for 0.55% (95% CI: 0.36–0.75) and 0.61% (95% CI: 0.37–0.84) of individuals, respectively. After adjusting for possible confounding factors, prevalence of early and late AMD increased with increasing age (OR = 1.35; 95% CI: 1.23–1.49 for early and OR = 3.01; 95% CI: 2.22–4.08 for late AMD, per each decade of age increase, p < 0.001). After adjustment for age, sex, family history, smoking history, hypertension, diabetes and BMI, subjects from the inland town presented a significantly higher OR of early and late AMD than subjects from the coastal town (OR = 2.57, 95% CI: 2.12–3.12, p < 0.001 for early and OR = 2.06, 95% CI: 1.07–3.95, p = 0.029 for late AMD). Conclusions: The prevalence of early and late AMD in this Portuguese population was similar to other large‐scale population‐based cohorts. After controlling for confounders, age and study site of inclusion were significant independent predictors for both early and late forms of the disease. Further analysis will be needed to completely unravel the underlying reasons for this difference regarding geographic location.